RANCANG BANGUN TEXT DAN ANIMASI 3 DIMENSI PADA LED CUBE BERBASIS ARDUINO UNO ATMEGA 328 - Muhammad Iqbal; Reza Nandika; Endang Susanti (Fakultas Teknik, Universitas Riau Kepulauan, 2019)
Promotion is one means to increase sales figures at a company. And the product being promoted. Promotions carried out to potential target markets. There are various kinds of promotional media used such as neon boxes. Neon Box requires neon lights with high electric power and high prices. On the other hand the neon box image is static or cannot be changed. So from the problems above, through this study the authors designed a promotional media using LEDs that were shaped like cubes. Because LED prices are not expensive. This promotional tool was built using an Arduino-based microcontroller and connected to the interface on the desktop. Display that can be arranged through the desktop are letters, numbers, and shapes (flat areas). CUBE LEDs were tested 5 times for each flame pattern and the test results were obtained successfully. So the CUBE LED was successfully designed and built and found no errors.